Effects of different periodontal interventions on the risk of adverse pregnancy outcomes in pregnant women: a systematic review and network meta-analysis of randomized controlled trials - Wu, Jianru; Wu, Jingying; Tang, Biyu; Zhang, Ze; Wei, Fenfang; Yu, Dingbiao; Li, Limin; Zhao, Yue; Wang, Bei; Wu, Wenyu; Hong, Xiang (Frontiers in Public Health, 2024)
Background Periodontal disease is widespread among pregnant women, and it is possible that taking action to improve oral health conditions can make improvements in adverse pregnancy outcomes. Herein, we summarize the recent evidence using a network meta-analysis to assess the effects of different periodontal treatment intervention strategies on the risk of adverse pregnancy outcomes in pregnant women. Materials and methods Randomized controlled trials were retrieved from PubMed, Web of Science, Embase, and Cochrane Library databases. After literature screening, data extraction, and quality evaluation of the included literature were performed, the R studio 4.2.2 “netmeta” package was used for the network meta-analysis. Results A total of 20 studies were included, and 5 adverse pregnancy outcomes (preterm birth, low birth weight, preterm birth and/or low birth weight infants, small for gestational age, and pre-eclampsia) were considered to examine the effects of different periodontal treatment interventions strategies on the risk of the abovementioned outcome indicators. The results of the network meta-analysis demonstrated that the three periodontal treatment intervention strategies of sub- and/or supra-gingival scaling and root planing + chlorhexidine rinsing (SRP + CR), sub- and/or supra-gingival scaling and root planing+chlorhexidine rinsing + tooth polishing and plaque control (SRP + CR + TP), and sub- and/or supra-gingival scaling and root planing +sonic toothbrush + tooth polishing and plaque control (SRP + ST + TP) reduced the risk of preterm birth [odds ratio (OR) = 0.29, 95% confidence interval (CI) (0.10–0.88), OR = 0.25, 95CI% (0.10–0.63), OR = 0.28, 95CI% (0.11–0.69), respectively]. In addition, two periodontal treatment intervention strategies, SRP + CR and SRP + CR + TP, were effective methods in terms of the risk of preterm birth and/or low birth weight [OR = 0.18, 95CI% (0.06–0.52), OR = 0.31, 95CI% (0.12–0.79)]. Conclusion The available evidence suggests that the risk of preterm birth and preterm birth and/or low birth weight can be reduced with certain periodontal treatment intervention strategies. Future studies should focus on optimizing intervention strategies and the optimal timing for different periods of pregnancy, in order to provide a reference for pregnant women’s healthcare. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=407901, CRD42023407901.